Implementasi Smart Parking System Berbasis Computer Vision Menggunakan IP Camera dan Integrasi Java Library Pada PT. Tri Alfa Sinar Mandiri - Nanda Diaz Arizona; Deasy Purwaningtias; Muhammad Iqbal (Jurnal Sistem Informasi Akuntansi, 2026)
PT. Tri Alfa Sinar Mandiri, as a public facility management company, faces challenges in parking management efficiency, where the previous system had limitations in real-time visual monitoring and relied heavily on manual operator input. This manual process often leads to queues and is prone to errors in recording physical vehicle data. This research aims to implement a Smart Parking System based on Computer Vision using IP Cameras directly integrated with a Java-based desktop application. Unlike previous developments that used the Waterfall method, this study applies the Prototyping method to facilitate iterative testing of camera hardware integration and image processing library accuracy. The system is designed to automatically capture video streams when a vehicle is detected, perform visual validation without physical interaction, and store image data into the database. Test results demonstrate that the integration of Java Libraries with IP Cameras successfully displays real-time monitoring and accelerates transaction processes at entry and exit posts. This implementation provides a modern solution that significantly improves security and operational efficiency compared to conventional systems